Gender trouble : feminism and the subversion of identity - Butler, Judith (Routledge, 1999)
Since its publication in 1990, Gender Trouble has become one of the key works of contemporary feminist theory, and an essential work for anyone interested in the study of gender, queer theory, or the politics of sexuality in culture.